If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(3y + -8) = 5 + -4y Reorder the terms: 6 + -1(-8 + 3y) = 5 + -4y 6 + (-8 * -1 + 3y * -1) = 5 + -4y 6 + (8 + -3y) = 5 + -4y Combine like terms: 6 + 8 = 14 14 + -3y = 5 + -4y Solving 14 + -3y = 5 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 14 + -3y + 4y = 5 + -4y + 4y Combine like terms: -3y + 4y = 1y 14 + 1y = 5 + -4y + 4y Combine like terms: -4y + 4y = 0 14 + 1y = 5 + 0 14 + 1y = 5 Add '-14' to each side of the equation. 14 + -14 + 1y = 5 + -14 Combine like terms: 14 + -14 = 0 0 + 1y = 5 + -14 1y = 5 + -14 Combine like terms: 5 + -14 = -9 1y = -9 Divide each side by '1'. y = -9 Simplifying y = -9
| -z=-4z+6 | | 6.4(x-4)=19.5 | | -w=-5w+16 | | 3z/4=2z/3-5 | | -10x=75 | | -8-b/5=-10 | | (2*x/((14/10)*x)=0 | | 9.2(x+6.4)=124.48 | | -2-k/2=-8 | | a/6+1=11 | | 8d-7=32 | | y/7-1=8 | | 10-8e=18 | | 1.5(c+7)=-37.35 | | (8x^2y)/(12x^4y^4) | | -7-5q=-47 | | 7-5q=-47 | | -86=4c | | 5(n-2)-(6-4n)=8n | | 9x+10-6x=9+2x-6 | | -6(X+9)=20 | | 5-p=9 | | 10x+(8x-16)+(12x-8)+(7x+2)+(9x+4)(6x+10)= | | x^2+5(3+13)=5x-3 | | 3-5(2-3)+7x=8x-3(2-2) | | 3y-4=12-5y | | 11x-67=43 | | 3^4/x=444 | | 2(g-8)=10 | | 2z/7-2=-1 | | 7/9v=21 | | 3m+7m-2m= |